Membaca Penguatan dalam Diam: Eksplorasi Praktik Natural Positive Reinforcement oleh Dosen Fisika - Ananingtyas, Ratika Sekar Ajeng; Prawitasari, Prawitasari; Hapsoro, Cahyo Aji; Sulur, Sulur; Kusairi, Sentot; Khusaini, Khusaini; Sujito, Sujito; Rohmiati, Dyah Palupi (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to explore naturally occurring practices of positive reinforcement in the learning process of Mathematical Physics 2 and their impact on students' motivation and understanding. The study employed a descriptive qualitative approach, with data collected through classroom observations, interviews with the lecturer, and student questionnaires. The results show that the most frequently appearing forms of reinforcement included verbal praise, the awarding of additional points, and constructive feedback. Student responses indicate that these reinforcements had a positive effect on their enthusiasm for learning and classroom engagement. However, students also emphasized the importance of transparency and fairness in the distribution of reinforcement. This study provides an initial contribution to understanding naturally emerging reinforcement strategies and their relevance for further development as systematic instructional approaches in higher education.